2020
DOI: 10.20396/bjos.v19i0.8659930
|View full text |Cite
|
Sign up to set email alerts
|

Economical treatment-related burden assessment of maxillofacial trauma among Ukrainians patients

Abstract: Aim: Quantitative evaluation of prognostic correspondence between initial maxillofacial traumatic injury assessed by facial injury severity score and maxillofacial injury severity score, treatment cost and duration of hospitalization among Ukrainian patients. Methods: Design of present study was retrospective and based on the medical data of patients hospitalized with signs of maxillofacial trauma. Quantitative assessment of maxillofacial trauma was held with the use of facial injury severity score (FISS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…Studies have identified the commonest mechanisms of injury in the maxillofacial region as; motor vehicle and motorcycle collisions [ 12 , 13 , 14 ], assault [ 8 , 15 , 16 ], and falls [ 17 , 18 ]. Additionally, MI has been identified as one of the commonest forms of injury in gender-based violence [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified the commonest mechanisms of injury in the maxillofacial region as; motor vehicle and motorcycle collisions [ 12 , 13 , 14 ], assault [ 8 , 15 , 16 ], and falls [ 17 , 18 ]. Additionally, MI has been identified as one of the commonest forms of injury in gender-based violence [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This disproportionality in association results from the lack of a functional injury surveillance system and the weakness in the medical certification of causes of death as per international classifications [ 42 ]. The economic burden emanates from the management and rehabilitation associated with restoring aesthetic, physical, and functional damage [ 12 , 33 ] on the individual and the healthcare system [ 16 , 33 , 43 ]. The average cost for managing combined maxillofacial traumas per patient ranges from $1716 to $24,004 in Turkey and Malaysia, respectively [ 33 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Вступ. Більшість доступних для аналізу досліджень, присвячених питанням епідеміології травм щелепнолицевої ділянки, є ретроспективними за своїм характером та були проведені на базі одного, рідко -декількох дослідницьких центрів (лікарень, клінік, відділень травматології), певного географічного регіону [1][2][3][4][5][6].…”
unclassified